(untitled) - The World Bank (Ha Noi, 2008)
This document is updated of the Northern Upland (Vietnam) Health Support Project by the World Bank. Project ID: P082672 (2008-2014). The content is consisted of project description; press release; PID; ISDS; safeguard reports; PAD; PD...
Keywords: Health service,Dịch vụ y tế